PENGARUH MOTIVASI, DISIPLIN KERJA, DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA UD. SRI MULYA ARJASA KABUPATEN SUMENEP - minullah minullah; karnadi Karnadi (Relawan Jurnal Indonesia, 2020)
This study aims (1) to determine the effect of motivation, work discipline, and work environment on employee work productivity (2) to determine the effect of motivation, work discipline, and work environment simultaneously influence on employee work productivity (3) to find out among motivations, work discipline, and the most dominant work environment influences employee work productivity. The method used is quantitative. The results of the study are multiple linear regression equation Y = 1.434E-16 + 0.249 X1 + 0.469 X2 + 0.336 X3 + e. partially motivation has a significant positive effect with tcount greater than ttable (2.335)> (2.018) or sig α 0.024 <0.05, work discipline shows tcount greater than ttable (4.454)> (2.018) or sig α 0.00 <0.05, the work environment shows that the t-test value is greater than table (3.152)> (2.018) or sig α 0.03> 0.05. Simultaneously motivation, work discipline, and work environment have an effect on employee work productivity with a Fcount of 19.209 values ​​greater than Ftable of 2.83 or Fcount of 19.209> Ftable of 2.83. The most influential dominant variable in this study is work discipline with a value of 4.454. R2 value of motivation, work discipline, and work environment variables of 57.8% and the remaining 42.2% is influenced by other factors not included in the study